If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+14=2x-11
We move all terms to the left:
3x+14-(2x-11)=0
We get rid of parentheses
3x-2x+11+14=0
We add all the numbers together, and all the variables
x+25=0
We move all terms containing x to the left, all other terms to the right
x=-25
| H(x)=2-5x | | 9920=x-0.2x | | 9x-3-2=18 | | 2x^+20x+80=9 | | X/12-3x=10 | | 150m-75m+55000=53625-200m | | 46-5m=2m-3 | | 4x+1=2(2x+3 | | 3(2x+4)+2(x-3)=46 | | 35/5=2m | | 1/5y-1=3 | | F(x)=3+7.5x | | Y=5x-3x=0 | | 2x=5x-59 | | 5(x+9)=-4x-51 | | 0.12n+0.06(4500-n)=0.07(4500) | | 6y-42=3(y-8) | | 5y=56 | | 4x/3-2=3x/2+6 | | 342/x-x=1 | | 2(w+3)=6w+26 | | x+3-7+8x*9=75 | | 56/n=156/39 | | 5x+40=62 | | 7x-8=-5(x+4) | | 46-8x=14 | | 5x-4=2-10x | | x^2-80x+1.5=0 | | m=-1/2(4,7) | | 9x+22=26 | | m=6(5,3) | | 7x−6=2x=17 |